Boundary Making in Myanmar's Electoral Process: Where elections do not take place. (14th March 2022) - LIDAUER, MICHAEL
Abstract: The 2015 general elections were considered a hallmark of Myanmar's transition from an authoritarian regime towards a new form of government. However, the elections did not take place in all parts of the country, and significant portions of the population were excluded from the vote, including voters in areas of contested sovereignty, those who experienced displacement by conflict, and the Rohingya. Against the background of the regulatory framework for elections in Myanmar and its electoral system, this article looks first into a particular understudied element of the electoral process—the cancellation or postponement of elections in areas affected by conflict, which is little understood by voters, election administrators, and outside observers. Second, the article examines the conditions necessary for internally displaced persons (IDPs) to participate in elections. Third, the article recapitulates the gradual legal disenfranchisement of voters and candidates who self-identified as Rohingya, which preceded their mass exodus to Bangladesh in 2017. While in 2015 all these processes of exclusion were arguably of lesser priority for the election administration, which facilitated the first credible Myanmar election in decades, they have not altered significantly since and will affect the electoral participation of disadvantaged communities again in the future.